Статическая оптимизация процесса каталитического риформинга - Левчук, И. Л. (НТУ "ХПИ", 2015)
На основе анализа входных и выходных координат выполнена постановка задачи статической оптимизации процесса каталитического риформинга, предложен способ решения этой задачи на основе метода нелинейной оптимизации Хука-Дживса. Проведено исследование оптимальных режимов процесса, предложен способ управления, обеспечивающий увеличение выхода катали-зата в среднем на 3-5 %.

Based on the analysis of input and output process coordinates, it was proved that the static mode is the basic operating mode of the catalytic reforming unit. The analysis of the process as a control object was carried out, the composition of the vector of input optimized values and the type of optimization criterion were determined. Formulation of the problem of static optimization of catalytic reforming process was made, and a method for solving this problem based on the Hooke-Jeeves non-linear optimization method, supplemented by the constraint verification procedure was proposed. To determine the sensitivity of the optimal conditions to the process perturbing effects, a series of one-factor experiments relative to the main level of perturbing effects, corresponding to the basic mode, not being optimal, was performed. According to the study of optimum modes, the control method of the reactor block of the catalytic reforming unit through the optimal temperature distribution at the inputs of the first and second reactors at a constant limitvalue of other control actions was proposed. Experimental testing of the proposed control method based on experimental data of the catalytic reforming unit of Odessa refinery has shown an increase in yield of the desired product - catalysate by 3-5% on average for all the studied basic modes.
Static optimization of catalytic reforming process
Keywords: нефтепереработка; катализат; базовые режимы; способ управления; oil refining; catalytic reforming; catalysate; static optimization; basic modes; control method